2021
DOI: 10.4314/tjpr.v20i10.14
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic and flavonoid contents, cytotoxic, immunomodulatory and anti-inflammatory potential of whole plant of Astragalus creticus (Fabaceae)

Abstract: Purpose: To determine total phenolic and flavonoid contents, as well as the cytotoxic, immunemodulatoryand anti-inflammatory potentials of the whole plant of Astragalus creticus (Fabaceae).Methods: Folin-Ciocalteu (FCR) method was used for determination of total phenolic and flavonoid contents of the methanol and dichloromethane extracts of Astragalus creticus. The cytotoxic potential of the extracts on 3T3 and HeLa cell lines were evaluated using MTT assay. Brine shrimp larvae mortality was determined by leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In particular, the TPC value for T. repens flowers extract is calculated as 192.0 mg GAE/g extract [ 50 ], a value significantly higher than the reported herein TPC values of 24.228 and 27.7 mg GAE/g for T. repens and T. physodes , pointing out their flowers as the primary source of phenolics. This assumption is reinforced by reports for the TPC of T. pratense ranging from 44.4 to 53.7 mg/kg of dry matter [ 40 ], values in line with present findings adjusted in accordance with their extract yield. The amounts of condensed tannins detected in seeds, flowers, and leaves of T. repens highlighted flowers having the highest content (13–79 mg/g) and leaves with poorest (not detected–0.6 mg/g).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, the TPC value for T. repens flowers extract is calculated as 192.0 mg GAE/g extract [ 50 ], a value significantly higher than the reported herein TPC values of 24.228 and 27.7 mg GAE/g for T. repens and T. physodes , pointing out their flowers as the primary source of phenolics. This assumption is reinforced by reports for the TPC of T. pratense ranging from 44.4 to 53.7 mg/kg of dry matter [ 40 ], values in line with present findings adjusted in accordance with their extract yield. The amounts of condensed tannins detected in seeds, flowers, and leaves of T. repens highlighted flowers having the highest content (13–79 mg/g) and leaves with poorest (not detected–0.6 mg/g).…”
Section: Discussionsupporting
confidence: 92%
“…A thorough literature review of previous research results concerning the studied Fabaceae plants verified that the TPC and TTC values for T. physodes and C. incisum extracts are reported herein for first-time. A similar observation also applies to the determination of L. laxiflorus TPC [ 38 ], A. creticus TPC [ 39 ], and TTC [ 40 ], C. arientinum TTC [ 41 ], B. bituminosa [ 42 , 43 ], and A. glycyphyllos TPC [ 44 ]. It must be noted that T. repens , a widely cultivated forage crop, comprises the only well-documented plant in the literature with numerous studies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Condensation of chromatin, visualized by acridine orange fluorescence, is one of the morphological alterations found during apoptosis. This results from the PAR extract effect, which merges infected cells with surrounding cells, resulting in multinucleated giant cells and cell death by apoptotic or nonapoptotic mechanisms in a variety of human malignant cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid glycosides can bind noncovalently to active site residues of enzymes and have variable structural properties, so they have the potential for the selective inhibition of α-glucosidase [ 14 ]. In addition, the literature has shown that extracts of Astragalus creticus, containing quercimeritrin among other secondary metabolites, demonstrated antioxidant potential and good inhibition of α-glucosidase enzyme [ 15 ]. Recent studies showed that other flavones, tricetin and genkwanin, exhibited α-glucosidase and α-amylase inhibitory activities, respectively [ 16 , 17 ], while linarin could prevent the action of α-glucosidase and α-amylase enzymes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%